2020
DOI: 10.1002/bimj.201900180
|View full text |Cite
|
Sign up to set email alerts
|

A regularized estimation approach for case‐cohort periodic follow‐up studies with an application to HIV vaccine trials

Abstract: This paper discusses regression analysis of the failure time data arising from case‐cohort periodic follow‐up studies, and one feature of such data, which makes their analysis much more difficult, is that they are usually interval‐censored rather than right‐censored. Although some methods have been developed for general failure time data, there does not seem to exist an established procedure for the situation considered here. To address the problem, we present a semiparametric regularized procedure and develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 35 publications
(68 reference statements)
0
9
0
Order By: Relevance
“…which implies that fðÁÞ is a contraction mapping from ½1=K 0 ; K 0 qþ1 to itself with probability tending to 1. Hence, according to the contraction mapping theorem, there exists one unique fixed-pointb (ii) From equation (19)…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…which implies that fðÁÞ is a contraction mapping from ½1=K 0 ; K 0 qþ1 to itself with probability tending to 1. Hence, according to the contraction mapping theorem, there exists one unique fixed-pointb (ii) From equation (19)…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…23 The value of m can be chosen by the cross-validation method, and in practice, one may perform grid search over some possible range of m or fix m to be the closest integer to n0.25. 19 Note that here Bernstein polynomials are chosen simply because of their natural monotone property and simplicity. Instead it is apparent that one could alternatively use other smooth functions such as B -spline functions and the proposed method could be similarly developed.…”
Section: Sieve Penalized Variable Selection Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…(2020) and Zhao et al . (2020b), who provided some justifications both numerically and theoretically.…”
Section: Variable Selection For Cox Proportional Hazards Modelmentioning
confidence: 99%
“…Also, as mentioned earlier, the algorithm is available at the R package CoxICPen with setting the weight argument to be the π i s. In addition, Zhao et al . (2020b) showed that the method with the use of the ALASSO penalty function has the oracle property. A limitation of the method is that it only applies to the situation with p < n .…”
Section: Variable Selection For Other Types Of Interval‐censored Datamentioning
confidence: 99%